2012
DOI: 10.1149/2.008302jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Zinc Ion Storage in Alpha Manganese Dioxide for Zinc Ion Battery by Electrochemical Impedance Spectrum

Abstract: The storage process of Zn 2+ ion into α-MnO 2 has been investigated by electrochemical impedance spectrum. A new phase formation process has been recognized. The equivalent circuit model and the impedance expression have been built up to characterize the storage of Zn 2+ ion into α-MnO 2 . It is found that the storage process of Zn 2+ ions is mainly determined by the phase change. With the decrease of potential, Zn 2+ ions begin to insert into MnO 2 and phase change occurs, which leads to a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
6
59
0
Order By: Relevance
“…The first impedance measurements of batteries appear to have been performed by Willihnganz in 1941. 5 Xu et al 6 investigated the process and monitored the phase change of the storage of Zn 2+ ions into α-MnO 2 by EIS. Arnott et al 7 examined the electrochemical and morphological changes that γ-MnO 2 undergoes during reduction in an alkaline manganese dioxide cathode.…”
mentioning
confidence: 99%
“…The first impedance measurements of batteries appear to have been performed by Willihnganz in 1941. 5 Xu et al 6 investigated the process and monitored the phase change of the storage of Zn 2+ ions into α-MnO 2 by EIS. Arnott et al 7 examined the electrochemical and morphological changes that γ-MnO 2 undergoes during reduction in an alkaline manganese dioxide cathode.…”
mentioning
confidence: 99%
“…Redistribution subject to ECS terms of use (see 18.236.120. 13 Downloaded on 2018-05-12 to IP anisotropic channel character, would not allow filling of a larger part of the vacant sites although the number of them is high in o-Mo 9 Se 11 . 21 On the other hand, in the case of Chevrel compounds, Mo 6 X 8 (X = S, Se), with three-dimensional diffusion channel, 33 it is reported that both Li-and Mg-systems show the similar order capacity comparable with the theoretical capacity 11,12,[17][18][19][20]34,35 deduced from the molecular orbital model, 23 in which extra four electrons per formula unit form closed-shell configuration of bonding orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In recent years, an effort for developing new energy storage systems, which use ion-insertion mechanism, is being invested also in nonlithium-ion battery systems, such as sodium-ion, 5,6 potassium-ion 7,8 and multivalent-ion batteries. [9][10][11][12][13][14][15][16] Among them, Mg-ion battery is one of the fascinating battery systems due to its possible low cost and safety, which could be realized by rich resource and moderate reactivity of magnesium. [9][10][11][12] However, in most materials, the strong electrostatic interaction between introduced Mg 2+ and host lattice, which is due to bivalence of Mg 2+ , induces the slow solid state diffusion of Mg-ions within the crystal lattice and hampers reversible electrochemical insertion/extraction of Mg 2+ .…”
mentioning
confidence: 99%
“…In addition, MnO 2 is the most widely used cathode, which can produce large discharge capacities, higher than 200 mAh g −1 with a practical potential of 1.3 V [2][3][4]. Until now, charge storage mechanism of MnO 2 has been only investigated in aqueous electrolytes, and two mechanisms have been proposed to explain it [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation of divalent cations, such as Mg 2+ and Zn 2+ , into MnO 2 have been recently reported, opening the development of an emerging energy storage system: Zn 2+ or Mg 2+ ion batteries as most viable candidates for replacing Li-ion batteries [2][3][4]8,9]. In this sense, Oh et al have published a series of papers describing the intercalation of Zn 2+ cations into different MnO 2 structures [4,8,9].…”
Section: Introductionmentioning
confidence: 99%